Molecular Epidemiology of Multiresistant Streptococcus pneumoniae with Both erm(B)- and mef(A)-Mediated Macrolide Resistance - Farrell, David J. (American Society for Microbiology, 2004)
Of a total of 1,043 macrolide-resistant Streptococcus pneumoniae isolates collected from 24 countries as part of PROTEKT 1999-2000, 71 isolates tested positive for both the mef(A) and erm(B) genes. Of 69 isolates subjected to further molecular investigations, all were resistant to tetracycline, 63 (91.3%) were resistant to penicillin, and 57 (82.6%) were resistant to trimethoprim-sulfamethoxazole. One isolate was also fluoroquinolone resistant, and another was resistant to quinupristin-dalfopristin. The ketolide telithromycin retained activity against all of the isolates. Of the 69 of these 71 isolates viable for further testing, 46 were from South Korea, 13 were from the United States, 8 came from Japan, and 1 each came from Mexico and Hungary. One major clonal complex (59 [85.5%] of 69 isolates) was identified by serotyping (with 85.5% of the isolates being 19A or 19F), pulsed-field gel electrophoresis, and multilocus sequence typing. The remaining isolates were less clonal in nature. Representative isolates were shown to carry the mobile genetic elements Tn1545 and mega, were negative for Tn1207.1, had tetracycline resistance mediated by tet(M), and contained the mef(E) variant of mef(A). All isolates were positive for mel, a homologue of the msr(A) efflux gene. These clones are obviously very efficient at global dissemination, and hence it will be very important to monitor their progress through continued surveillance. Telithromycin demonstrated high levels of activity (MIC for 90% of the strains tested, 0.5 μg/ml; MIC range, 0.06 to 1 μg/ml) against all isolates.